Analysis of Mathematical Problem-Solving Abilities of Elementary School Students Based on Learning Interests and Gender - Darojatun Nasihah; Hesti Yunitiara Rizqi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Mathematical problem-solving is a fundamental competence in elementary mathematics because students must not only obtain correct answers but also understand problems, formulate appropriate strategies, execute solution procedures, and evaluate their results. This study aimed to analyze the mathematical problem-solving abilities of fourth-grade elementary school students according to learning interest and gender. A descriptive qualitative approach was employed involving 19 students, comprising 9 boys and 10 girls. Data were collected through a learning interest questionnaire, a mathematical problem-solving response questionnaire, written tests, semi-structured interviews, and documentation. Six students were purposively selected to represent high, moderate, and low learning interest categories across genders. Their problem-solving processes were examined using Polya’s four stages: understanding the problem, devising a plan, carrying out the plan, and looking back. The findings showed that students with high learning interest successfully completed all four stages, whereas those with moderate learning interest demonstrated inconsistencies, particularly in implementing solution plans and reviewing their answers. Students with low learning interest experienced more extensive difficulties in devising plans, carrying out solutions, and verifying results. Gender did not reveal a consistent pattern of superiority because differences in performance occurred within each learning interest category. The study also identified discrepancies between students’ positive questionnaire responses and their actual written-test performance. These findings indicate that mathematical problem-solving ability is more closely associated with learning interest and individual problem-solving processes than with gender alone. This study contributes to elementary mathematics education by emphasizing the need for instructional strategies that strengthen students’ learning interest, provide structured support across Polya’s problem-solving stages, and accommodate individual differences in problem-solving performance.